El compromiso organizacional de la generación millennial y la generación z en la Cooperativa de Ahorro y Crédito CREDI YA LTDA - Robles Ortiz, Alejandra Monserrath (2024)
The objective of this study was to determine the level of organizational commitment of the millennial generation and generation z at Credi Ya Savings and Loan Cooperative. Emotional intelligence has been considered an essential component to effectively manage interpersonal conflicts. Organizational commitment worldwide presents a medium to low level according to studies conducted in recent years, according to (Davis & Needham, 2023) was studied in a US Hospital reaching the conclusion that there is a low level of organizational commitment due to generational differences. By means of a quantitative research approach and a documentary-bibliographic and descriptive typology. To carry out the research, the Allan & Meyer (1991) instrument was used, which consists of three dimensions: affective, continuity and normative commitment. The study population included 67 participants, distributed in 30 employees of the millennial generation and 37 of the z generation. The results revealed a level of organizational commitment of 13.81% for the millennial generation and 14.09% for generation Z, which are considered low, since the threshold for high commitment starts at 21%. Finally, we have developed proposals for strategies to increase the development of personal relationships and generate emotional bonds within the organization, with this we conclude that there is no difference in organizational commitment of the two generations of study and it is essential to continue with studies about the retention of generational staff.